Законодавство України про сільськогосподарську кооперацію: проблемні питання та шляхи їх вирішення - Тропін, Віталій Валерійович; Tropin, Vitalii (Дніпровський державний аграрно-економічний університет, 2016)
Розглянуто деякі актуальні питання, що потребують негайного вирішення та нормативного закріплення, зокрема щодо єдиного підходу до визначення членів сільськогосподарського обслуговуючого та сільськогосподарського виробничого кооперативів; усунення ухилу правового регулювання у бік сільськогосподарської обслуговуючої кооперації та нехтування питаннями розвитку кооперації виробничої; врегулювання питання визначення та формування статутного капіталу сільськогосподарського кооперативу; усунення недоліків підзаконного нормативноправового регулювання сільськогосподарської кооперації; вдосконалення механізму реєстрації сільськогосподарського обслуговуючого кооперативу як неприбуткової організації тощо. The article investigates issues of current legislation regulating the establishment and operation of agricultural cooperatives, and developing ways to improve them. Proved that the efficiency of agricultural production of different types of business entities in the agricultural sector depends on proper legislative support of their legal status, the maximum consideration of the specifics of their production activities in the regulation. We consider some urgent issues that need urgent attention and regulatory consolidation, in particular regarding: a unified approach to the determination of the members of the agricultural service and agricultural production cooperatives; eliminating bias towards regulation of agricultural service cooperatives, and the neglect of issues of industrial development cooperation; determination and settlement of the authorized capital of the agricultural cooperative; deficiencies by-law legal regulation of agricultural cooperatives; improve the mechanism of registration of agricultural service cooperative as a non-profit organization and so on.Attention is paid to the different approach of the current legislation to regulate various aspects of agricultural production and agricultural service cooperatives. Developed and proposed conclusions on improving legislation aimed at regulating cooperative relations.
Law of Ukraine on agricultural cooperation: challenges and solutions
Keywords: законодавство; law; сільськогосподарська кооперація; agricultural cooperative activity; сільськогосподарський кооператив; agricultural cooperatives; членство; membership; неприбутковість; non-profit status; статут; charter document